Meat hybrids–An assessment of sensorial aspects, consumer acceptance, and nutritional properties - Baune, Marie-Christin; Broucke, Keshia; Ebert, Sandra; Gibis, Monika; Weiss, Jochen; Enneking, Ulrich; Profeta, Adriano; Terjung, Nino; Heinz, Volker (Frontiers in Nutrition, 2023)
So-called meat hybrids are a new class of products where a fraction of the meat product (e.g., 20 %) is replaced with alternative protein sources, such as plant-based ones. Research suggests that these products could serve as a low-threshold offer for a specific target group that wants to cut down on meat, thereby facilitating the transition towards a more healthy and sustainable diet. Nonetheless, data demonstrate that meat hybrids with a high substantial meat substitution level often fail in the market. This study summarises findings on the physicochemical properties, sensory, and acceptance of six different meat hybrids (70 % meat, 30 % plant proteins) that were collected in the framework of a case study in the project AiF 196 EN. For this purpose, sensory characteristics were collected via two QDA sessions and a hedonic consumer test. Furthermore, the hybrid recipes were analysed in their proximate composition. The respective recipes varied in protein source (soybean, pumpkin, pea) and mode of incorporation (textured vegetable protein (TVP), high moisture extrudate (HME)). It was shown that a meat hybrid with a relatively high share of 30 % plant-based proteins with peas as a protein source and TVP as a processing method can still attract consumers.